Systematic Literature Review: Implementation of Blended Learning in Science Education at Elementary Schools - Kurniawan, Gilang; Khairunnisa, Elvira; Winda, Esis; AS, Fadly; Dwi Jayanti, Zulaikhah (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Science learning requires teachers to be more creative and innovative in using information technology to support students' independent learning at home. One method that teachers can use to increase student independence in learning is the blended learning method. This research aims to analyze the implementation of blended learning in improving student learning outcomes in science education. This study employs the Systematic Literature Review method by reviewing international and national journals published in the last five years. The sample for this research consists of 11 journals that discuss blended learning, focusing on its impact on student learning outcomes in science education at the elementary school level. Data were obtained by summarizing the findings and analyzing the data. The results of the data analysis indicate that the average pre-test score is 63.56, while the average post-test score is 81.24. This demonstrates that the implementation of blended learning has been proven to improve students' science learning outcomes. In conclusion, the blended learning method is effective in improving learning outcomes and can be applied to other subjects at school.